Filterability of polysulfone membrane in a tilted panel system for activated sludge filtration - Ismail, A.A.A. (MDPI AG, 2020)
Membrane bioreactors (MBRs) are established technology for treatment of domestic and industrial wastewater because they offer a small footprint and high quality of effluent, in addition to lower excess sludge. However, their widespread applications are still limited by higher expenditure for compensating for membrane fouling. In this study, polysulfone (PSF)-based ultrafiltration membranes were developed and integrated with a tilted panel system for fouling control in activated sludge filtration. The results show an enhanced performance of filtration system thanks to the mutual advantage of the tilted panel system and the membrane properties. Both membranes showed a clear trend of higher permeability with respect to the tilted panel parameters, namely, higher tilting angle, higher aeration rate, and shorter intermittent/switching period. PSF-1 (1 wt polyethylene glycol (PEG) additive) shows significantly better performance than PSF-3 (3 wt PEG additive) although their mean flow pore size, structural properties, and contact angle do not differ significantly. PSF-1 shows superior filterability performance of about 45 for panel tilting angles of 20â¦ at an aeration rate of 1.8 LÂ·minâ1, and 11 for a switching period of 1 min compared with PSF-3. The key property enhancing the performance of the PSF-1 is its narrower distribution of pore size. Overall results suggest that an optimum system could be achieved by optimizing both the filtration system and the membrane material properties. Â© 2020 by the authors. Licensee MDPI, Basel, Switzerland.